This preview shows page 1. Sign up to view the full content.
Unformatted text preview: p ( E ) p ( F | E ) . However, p ( E ∩ F | E ) = p ( F | E ) 6 = p ( E ) p ( F | E ) , unless p ( E ) is 1, which is not true from (a). Thus the events of part (a) and part (b) are not independent. (d) E ( X ) = 7 X k =0 k · C (16 ,k ) C (36 , 7-k ) C (52 , 7) = 28 13 1...
View Full Document
This note was uploaded on 06/07/2011 for the course COT 3100 taught by Professor Staff during the Summer '08 term at University of Florida.
- Summer '08